2016
DOI: 10.1007/s11120-016-0326-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of elevated temperatures on specific leaf weight, stomatal density, photosynthesis and chlorophyll fluorescence in soybean

Abstract: High-temperature stress is a major environmental stress and there are limited studies elucidating its impact on soybean (Glycine max L. Merril.). The objectives of present study were to quantify the effect of high temperature on changes in leaf thickness, number of stomata on adaxial and abaxial leaf surfaces, gas exchange, chlorophyll fluorescence parameters and seed yield in soybean. Twelve soybean genotypes were grown at day/night temperatures of 30/22, 34/24, 38/26 and 42/28 °C with an average temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 41 publications
4
66
1
1
Order By: Relevance
“…It has been proven that girdling reduced maximal quantum yield of PSII photochemistry (Fv/Fm) (Nebauer et al 2011) and extremely few leaves results in a lower value of PN (Quentin et al 2013). Similar to other reports (Marini and Barden 1981, Thompson et al 1996, Jumrani et al 2017, the PN measured in the present study was positively correlated with SLM (Table 2), which is an important index of leaf development. The reduction in the PN of shoots with low LFRs (2L:3F and 1L:3F), along with the low Chl content and SLM values indicated that girdled shoots with extremely few leaves produced insufficient photosynthetic products to meet both their own requirement and a high fruit load, and that girdling blocked the transport of organic nutrients from other parts to the girdled shoot.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been proven that girdling reduced maximal quantum yield of PSII photochemistry (Fv/Fm) (Nebauer et al 2011) and extremely few leaves results in a lower value of PN (Quentin et al 2013). Similar to other reports (Marini and Barden 1981, Thompson et al 1996, Jumrani et al 2017, the PN measured in the present study was positively correlated with SLM (Table 2), which is an important index of leaf development. The reduction in the PN of shoots with low LFRs (2L:3F and 1L:3F), along with the low Chl content and SLM values indicated that girdled shoots with extremely few leaves produced insufficient photosynthetic products to meet both their own requirement and a high fruit load, and that girdling blocked the transport of organic nutrients from other parts to the girdled shoot.…”
Section: Discussionsupporting
confidence: 90%
“…Leaf traits determination: SLM was measured according to Jumrani et al (2017). Leaf squares (2 cm 2 ) were oven dried at 70°C for 3 h to obtain dry mass.…”
Section: Gas-exchange Measurementsmentioning
confidence: 99%
“…Photosystem II plays a key role in the response of leaf photosynthesis to environmental stresses, and PhiPSII measures the proportion of light absorbed by chlorophyll associated with PSII that is used in photochemistry (Jumrani et al, 2016). Iron deficiency could lead to decreases in lightharvesting pigments, particularly chlorophylls (Morales et al, 2000), and promotes antenna disconnection in PSII (Morales et al, 2001).…”
Section: Interaction Between Genotypic Tolerance and Soybean Growth Umentioning
confidence: 99%
“…In addition to the reversible modification of stomatal apertures, plants in the longer term can adapt their stomatal development to optimize their stomatal conductance g s to the surrounding environmental conditions, such as light intensity or CO 2 concentration (Casson & Gray, 2008). At high temperature, some plant species can produce leaves with altered stomatal density, which can affect transpiration rates and evaporative cooling (Crawford et al, 2012;Jumrani et al, 2017). Currently, however, it is not known whether rice stomatal development is affected by growth temperature.…”
Section: Introductionmentioning
confidence: 99%